2023
DOI: 10.5194/egusphere-2023-353
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A neural network-based method for generating synthetic 1.6 μm near-infrared satellite images

Abstract: Abstract. This study presents an extension to the method for fast satellite image synthesis (MFASIS) to allow simulating reflectances for the 1.6 μm near-infrared channel based on a computationally efficient neural network with improved accuracy. Such a fast forward operator enables using 1.6 μm channels from different satellite instruments in applications like model evaluation or operational data assimilation. It thus paves the way for the exploitation of additional information at this frequency, e.g. on clou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Similar approaches based on MLP were presented in (Stegmann et al, 2022). They were also used to emulate 3D effects on RT (Meyer et al, 2022) and to generate near-infrared satellite images (ρ 1 : 1.6 µm) in (Baur et al, 2023). Recently, Liang et al (2023) used ML to assimilate different bands of BT from Advanced Microwave Sounding Unit-A.…”
Section: Radiative Transfer Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar approaches based on MLP were presented in (Stegmann et al, 2022). They were also used to emulate 3D effects on RT (Meyer et al, 2022) and to generate near-infrared satellite images (ρ 1 : 1.6 µm) in (Baur et al, 2023). Recently, Liang et al (2023) used ML to assimilate different bands of BT from Advanced Microwave Sounding Unit-A.…”
Section: Radiative Transfer Modelsmentioning
confidence: 99%
“…Shi et al (2018) and Geiss et al (2021) analyzed the influence of clouds related parametrization on visible and infrared satellite images and found that the accuracy is closely related to the cloud representation. A further study about the impact of surface and air pressure and water and ice clouds on visible and near-infrared bands can be found in Baur et al (2023).…”
mentioning
confidence: 99%